PERANAN MAHKAMAH KONSTITUSI DALAM MENJAGA TEGAKNYA CITA HUKUM (RECHTS IDEE) PANCASILA DALAM BERNEGARA - Fais Yonas Bo'a (Arena Hukum, 2020)
AbstractAside from being a guardian of the constitution, the Constitutional Court also serves as a guardian of Pancasila by upholding Pancasila as a legal ideal (rechtsidee). The enforcement of such ideals is a progressive step of the Constitutional Court in the midst of erosion of the easiness and relevance of the ideals of Pancasila. The pursuit of Pancasilaâ€™s legal ideals is characterized by two things: fi rst, the widespread judicial review of the law due to the poor quality of the law which is certainly a refl ection of the understanding of lawmakers about the ideals of Pancasila as a guideline as well as the purpose of punishment. Second, the fragile identity of the national legal system due to the pluralism of the legal system so that there are many legal identities. As a result, Pancasila as the national legal identity is increasingly marginalized. However, through the Constitutional Courtâ€™s decision to make Pancasila a â€œtest stoneâ€, the existence of the ideals of Pancasila is always upheld. Thus, the Constitutional Courtâ€™s decision attaches Pancasila as the ideals of national law. On the other hand, the decision of the Constitutional Court also becomes a refl ection for lawmakers in the future to pay more attention to the quality that is guided by the ideals of Pancasila. In addition, for the national legal system to be more complete so that Pancasila as the identity of the national legal system is not marginalized.AbstrakSelain sebagai pengawal konstitusi, Mahkamah Konstitusi juga berperan sebagai pengawal cita hukum (rechtsidee) Pancasila. Penegakkan cita hukum tersebut sebagai langkah progresif MK di tengah tergerusnya ekisistensi dan relevansi cita hukum Pancasila. Tergerusnya cita hukum Pancasila ditandai oleh dua hal yaitu: pertama, semakin maraknya judicial review undang-undang yang disebabkan oleh rendahnya kualitas undang-undang yang tentu menjadi cerminan rendahnya pemahaman para pembuat undang-undang tentang cita hukum Pancasila sebagai pedoman sekaligus tujuan dalam berhukum. Kedua, rapuhnya identitas sistem hukum nasional yang disebabkan oleh adanya pluralisme sistem hukum sehingga terdapat banyak identitas hukum. Akibatnya, Pancasila sebagai identitas hukum nasional semakin termarginalkan. Namun, melalui putusan MK yang senantiasa menjadikan Pancasila sebagai â€œbatu ujiâ€, cita hukum Pancasila ditegakkan. Dengan demikian, putusan MK merekatkan Pancasila sebagai cita hukum nasional. Pada sisi lain, putusan MK juga menjadi tuntutan bagi pembuat UU agar ke depan lebih memperhatikan kualitas yang berpedoman pada cita hukum Pancasila. Terutama pula, agar sistem hukum nasional lebih utuh sehingga Pancasila sebagai identitas sistem hukum nasional tidak termarginalkan.